Propuesta de documentación para la elaboración del plan estratégico de consumo responsable de alcohol en el restaurante Gastro -Bar PIURA de la ciudad de Neiva para el 2022 - Galvis Robles, Paula Julieth (Universidad Antonio Nariño, 2022)
This degree work was carried out with the objective of developing a proposal of documentation for the development of the strategic plan for responsible alcohol consumption in the restaurant Gastro-Bar PIURA in the city of Neiva for 2022, the study is a descriptive non-experimental type, which works on factual realities associated with the level of compliance they have against the policy of prevention of responsible alcohol consumption. The results indicated that the company only complies with 30% of these requirements, therefore, it was necessary to elaborate a plan proposal based on three pillars composed of the definition of promotion actions, articulation spaces and service routes with the municipal support entities and the design of a monitoring and evaluation system of the Plan; it is concluded that for the implementation of the plan it is necessary to comply with the components of the guide given by the Ministry of Health.